High specific strength steel as an alternative material for heavy vehicle chassis – an explicit analysis. Issue 1 (March 2021) - Aathira, K U; Keerthi, V C; Arjun, S; Kiran, S J; Ramesh, S
Abstract: The chassis frame forms the backbone of a heavy vehicle which carries the load for all designed operating conditions. An important consideration in chassis design is adequate bending stiffness along with strength for better handling characteristics. Maximum shear stress and deflection are the important criteria in chassis design. The present paper is on the design of heavy vehicle chassis and its strength and rigidity analysis. In the analysis under identical load conditions, currently used chassis materials like low and medium carbon steels and cast iron are compared with high specific strength steel which can be an effective substitute material for the chassis. High specific strength steel has low density and possesses high strength properties. The dimensions of an existing vehicle chassis of AMW 2523 TP truck is taken for analysis. Rectangular Box type cross section is considered as it is observed to undergo least deflection. For validation the design is done by applying the vertical loads acting on different horizontal cross sections. The modelling and analysis are performed using SOLIDWORKS 2016 and ANSYS16.0. The results show that HSSS has the least deformation and stress induced and the proposed material provides enough strength and rigidity to the chassis.